Visual Working Memory for Faces and Facial Expressions as a Useful “Tool” for Understanding Social and Affective Cognition - Gambarota, Filippo; Sessa, Paola (Frontiers in Psychology, 2019)
Visual working memory (VWM) is one of the most investigated cognitive systems functioning as a hub between low- and high-level processes. Remarkably, its role in human cognitive architecture makes it a stage of crucial importance for the study of socio-affective cognition, also in relation with psychopathology such as anxiety. Among socio-affective stimuli, faces occupy a place of first importance. How faces and facial expressions are encoded and maintained in VWM is the focus of this review. Within the main theoretical VWM models, we will review research comparing VWM representations of faces and of other classes of stimuli. We will further present previous work investigating if and how both static (i.e. ethnicity, trustworthiness and identity) and dynamic (i.e. facial expressions) faces features are represented in VWM. Finally, we will examine research showing qualitative differences in VWM for face representations as a function of psychopathology and personality traits. The findings that we will review are not always coherent with each other, and for this reason we will highlight the main methodological differences as the main source of inconsistency. Finally, we will provide some suggestions for future research in this filed in order to foster our understanding of representation of faces in VWM and its potential role in supporting socio-affective cognition.